A photographic match of a western gray whale between Sakhalin Island, Russia, and Honshu, Japan: the first link between the feeding ground and a migratory corridor - Weller , David W.; Bradford, Amanda L.; Kato , Hidehiro; Bando , Takeharu; Otani , Seiji; Burdin , Alexander M.; Brownell Jr., Robert L. (J. Cetacean Res. Manage., 2023)
Between 2005 and 2007, four female western gray whales were accidentally entrapped and died in Japanese set nets while migrating along the Pacific coast of Honshu, Japan. Photographs of these animals were compared to a photo-identification catalogue of western gray whales from their feeding ground off Sakhalin Island, Russia, to look for matches of individuals between the two areas. Although useable quality photographs were available for only one of the four whales from Japan, a confirmed match was made to a whale photographed off Sakhalin Island. This match represents the first link between the feeding ground and a migratory corridor and highlights the importance of multinational research collaboration in the formation of range-wide conservation measures to protect this critically endangered population.